COMPARATIVE ANALYSIS BETWEEN AHP MOORA AND AHP-ELECTRE METHOD FOR OPTIMAL ELECTRIC AND SOLAR-POWERED SHIPYARD SITE SELECTION - Ispandiari, Ade Ratih; Yustina, Nanda; Qonita, Zulfa; Shabrina, Nurul; Gutami, Nanda Itohasi; Rochyntawati, Annissa; Iskendar, Iskendar (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Transportation is the second largest emitter of CO2 in the world, accounting for 25% of total CO2 emissions. To achieve a zero-carbon shipping industry, Indonesia can use its high sun exposure to generate electrical energy by using solar cell technology, which converts solar energy into electrical power. To answer the challenge, this research will start with the site selection of electric and solar-powered shipyards. This research tries to solve the problem of selecting the best location for electric and solar-powered shipyards by using the Multi-Criteria Decision Making (MCDM) method. The purpose of this research is to get the optimal location of electric and solar shipyards using AHP-MOORA and AHP-ELECTRE methods. There are three alternative locations in the location selection. Alternatives 1 and 3 are in Paciran District, Lamongan Regency, East Java Province, and alternative 2 is in Serang Regency, Banten Province. Alternative site 1 has an area of 38 ha and is located in Sidokelar Village, Paciran Sub-district. Decision-makers determine the parameters that will be evaluated from each alternative location, such as slope, soil type, rainfall, and 18 other criteria. In determining the weighting of parameters, a method that has a consistency test is needed so that the weight results obtained are consistent and objective. The study result shows that alternative location 1 is the best location for the electric and solar-powered shipbuilding industry, the same conclusion using the AHP-MOORA Integration approach and the AHP weighting ELECTRE Integration approach.